(untitled) - Bodie, Zvi (Boston, 2008)
This is the leading textbook for the graduate/MBA investments market. It is recognized as the best blend of practical and theoretical coverage, while maintaining an appropriate rigor and clear writing style. Its unifying theme is that security markets are nearly efficient, meaning that most securities are usually priced appropriately given their risk and return attributes. The text places greater emphasis on asset allocation, and offers a much broader and deeper treatment of futures, options, and other derivative security markets than most investment texts.
Keywords: Investments,Portfolio management,Quản lý vốn đầu tư,Đầu tư